(untitled) (Medico Legal Update, 2020)
Angle’s class II division 1 malocclusion, being the most commonly occuring type of malocclusion, is challenging to treat especially when there is an underlying skeletal discrepancy. Various fixed functional appliances have been developed over the years by different authors for correction of skeletal class II malocclusion due to retrognathic mandible. Among the fixed functional appliances available for class II correction, Advansync2 (Ormco Co, Glendora, Calif) also known as molar to molar appliance has been used effectively in the recent past. It is a fixed tooth-born functional appliance with an advantage of allowing concurrent use of fixed orthodontic therapy. This facilitates reduction of the overall treatment duration. Two case reports of patients treated using the Advansync2 class II corrector has been presented along with the skeletal and dentoalveolar changes observed during the treatment. The effects observed were similar to most fixed functional appliances however the treatment duration was considerably reduced in all the cases.